Modelling climate change impacts on wet and dry season rice in Cambodia - Alvar‐Beltrán, Jorge; Soldan, Riccardo; Ly, Proyuth; Seng, Vang; Srun, Khema; Manzanas, Rodrigo; Franceschini, Gianluca; Heureux, Ana (Journal of agronomy and crop science (1986), 2022)
Irregular rainfall, rising temperatures and changing frequency and intensity of extreme weather events are projected to reduce crop yields and threaten food security across the tropical monsoon sub‐region. However, the anticipated extent of impact on crop yields and crop water productivity (CWP) is not yet thoroughly understood. The impacts of climate change on rice yields and CWP are assessed over the Northern Tonle Sap Basin in Cambodia by applying the AquaCrop model into the mid‐ (2041–2070) to long‐future (2071–2099) under two Representative Concentration Pathways (RCPs) (4.5 and 8.5). Short (95 days), medium (125 days) and long (155 days) cycle varieties are tested during the wet and dry seasons. An assessment of different sowing dates and irrigation strategies (fixed and net irrigation during the dry season) elucidated the variation in response to changing environmental conditions. Higher yields (+15% by 2041–2070 and +30% by 2071–2099) and CWP values (+42% by 2071–2099) are expected if using short‐cycle varieties, in particular when sown in July. Dry season rice yields are also projected to increase (+28% by 2071–2099), especially under a higher greenhouse gas emission scenario (RCP 8.5) compared to a medium emission scenario (RCP 4.5) as a result of the CO2 fertilization effect. Depending on the climatic scenario, rice variety, irrigation scheme, and sowing date, increasing heat and drought‐stress conditions are likely to have different impacts on rice yields and CWP over time. Overall, this study highlights the benefits of adjusting crop calendars to identify the most suitable irrigation schedules and rice varieties to effectively adapt to projected future climate.